DEMOGRAPHIC FACTORS AND LIFE SATISFACTION: A STUDY AMONG INDUSTRIAL FEMALE OPERATORS - Khairani, Kamarulzaman bin Mahmad; Wahab, Muhammad Nubli Abdul; Sukadarin, Ezrin Hani; Sutarto, Auditya Purwandini (jfpublisher, 2023)
Employee well-being is crucial thing to performance and organizational success which has been studied extensively in the field of industrial and organizational psychology. Those employees with higher levels of well-being are less probable to quit and are typically more productive at the workplace. Therefore, the objective of this research is to examine the effect of several demographic factors on well-being such as life satisfaction among industrial female operators. There were 313 employees of an electronic component manufacturing company who participated in this research. A Life Satisfaction Scale consisting of five questions regarding the global cognitive evaluation of one's life was administered. The collected demographic factors were age, tenure, department or division, and dependents. The results indicated that tenure and marital status were related to life satisfaction. Those who are married and work longer in the company have a higher level of satisfaction than their peers. Meanwhile, the age, department, and dependents were not significant determinants of life satisfaction. Our research indicates the importance of implementing various strategies to improve life satisfaction, especially among newly recruited employees.